Fetotoxicity caused by the interaction between zinc and arsenic in mice - Fascineli, M. L.; Hunter, E. S.; Kempinas, W. D. (Wiley-Blackwell, 2002)
Arsenic is an environmental pollutant that induces congenital malformations in experimental models and can contribute to human birth defects. The environmental exposure to arsenic is relatively small when compared with the doses required to cause teratogenicity in mice and other laboratory animals. In order to study the action of zinc in the arsenic-induced teratogenicity, in the present work mice were either pretreated with zinc and later with arsenic or were treated simultaneously with zinc and arsenic in vivo and in vitro. Following administration of arsenate on gestation day 8, pregnant females were killed on the 17th day of gestation; maternal and fetal data were collected by laparotomy and used to calculate reproductive parameters. Fetuses were analyzed for the presence of external malformation and, after the appropriate processing, visceral and skeletal analyses were accomplished. Conceptuses were exposed in whole embryo culture to arsenicals on gestation day 8 (3-6 somite stage). After a 26 h culture period, morphological development was assessed. Neither pretreatment with zinc nor simultaneous administration of zinc prevented arsenic teratogenicity in these experimental models. (C) 2002 Wiley-Liss, Inc.
Keywords: heavy metals interaction; dysmorphology; whole embryo culture; arsenicals; teratogenicity